1998
DOI: 10.22358/jafs/69979/1998
|View full text |Cite
|
Sign up to set email alerts
|

The effect of digest acid on growth rate and some blood parameters in calves

Abstract: Analyses were carried out of the growth rate and concentration of some metabolites in blood serum of calves. The animals were fed diets supplemented with digest acid (a mixture of lactic, citric and orthophosphoric acids). It was shown that diet supplementation with this acid, used from calf birth till day 84 of life, had a beneficial effect on animal growth and increased uptake of the com pound mixture already from day 22 of life.When the animals were fed only solid feeds, acid supplementation improved nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Increasing the calf blood total lipids concentration as affected by DT indicated a pronounced relationship of easily digestible components availability in colostrum or milk (Strusinka et al, 1998). In our study, the treatment of dams with the combination of YC and LB had positive effects on calves performance, hematology, metabolites, enzyme activity, thyroid hormone, immunity, and antioxidant capacity more than calves of YC or LB alone.…”
Section: Discussionsupporting
confidence: 51%
“…Increasing the calf blood total lipids concentration as affected by DT indicated a pronounced relationship of easily digestible components availability in colostrum or milk (Strusinka et al, 1998). In our study, the treatment of dams with the combination of YC and LB had positive effects on calves performance, hematology, metabolites, enzyme activity, thyroid hormone, immunity, and antioxidant capacity more than calves of YC or LB alone.…”
Section: Discussionsupporting
confidence: 51%
“…These researches demonstrated that Ast supplementation could facilitate the large yellow croaker larvae to growth well. Combined with the truth that growth performance was associated with digestive ability and antioxidant capacity (Jiang et al, 2011; Strusinka et al, 1998), the promotion effect of Ast on growth performance of large yellow croaker larvae may be due to its ability on improving the digestive and antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…As affected by YC treatment, the present results are in accordance with those reported by Burdick Sanchez et al (2014), who indicated marked alterations in blood energy metabolites as affected by YC then it improve immune status. The increase in total lipids concentration in blood serum of primi-parous cows and their calves in G3 was attributed with improve digestibility of nutrients that increased the availability of digestible components in suckled milk for calves (Strusinka et al, 1998). In addition, increasing glucose level in cows and their calves of G3 may be attributed with gluconeogenesis improvement then lactose absorption increase (De Valdez et al, 1997).…”
Section: Blood Biochemical Concentrationsmentioning
confidence: 99%